НАУЧНЫЙ ТЕКСТ В КУЛЬТУРНО-РЕЧЕВОМ АСПЕКТЕ: ЭПИСТЕМИЧЕСКАЯ ТОЧНОСТЬ (ПОЛНОТА ИЛИ ЛАКОНИЗМ?) - Котюрова, Мария (Studia Rossica Posnaniensia, 2008)
The author analyzes the problems dealing with a scientific text editing. Depicting and discussing the ways and means serving the realization of functional-stylistic norms of a scientific text are the basic aim of the analysis.